University curricula and employability: The stakeholders' views for a future agenda. Issue 5 (October 2020) - Pereira, Elisabeth T.; Vilas-Boas, Madalena; Rebelo, Cátia F.C.
This article explores which measures are perceived by European key stakeholders (students, employers and academics) as crucial for the development of curricula that provide graduates with working-life competences and key skills that may increase their employability. It also seeks to identify measures that may strengthen cooperation between companies and universities. This was achieved through the application of 1734 questionnaires to key stakeholders in five European countries which are part of the European project #Europehome. The most popular measure identified by all stakeholders was the internship. More specifically, internships are considered of great importance to increase graduates' employability as well as being the best means of cooperation between universities and companies. In addition, the study identified a range of best practices and measures that may help lay the foundations and sustain the development of well-planned curricula.